ADHD as a Risk Factor for Infection With Covid-19 - Merzon, Eugene; Manor, Iris; Rotem, Ann; Schneider, Tzipporah; Vinker, Shlomo; Golan Cohen, Avivit; Lauden, Ari; Weizman, Abraham; Green, Ilan (Journal of attention disorders, 2021)
Background: ADHD limits the ability to comply with Covid-19 prevention recommendations. We hypothesized that ADHD constitutes a risk factor for Covid-19 infection and that pharmacotherapy may lower that risk. Methods: Study population included all subjects (N = 14,022) registered with Leumit Health Services between February 1st and April 30, 2020, who underwent at least one Covid-19 test. Data were collected from the electronic health records. Purchasing consecutively at least three ADHD-medication-prescriptions during past year was considered drug-treatment. Results: A total of 1,416 (10.1%) subjects (aged 2 months–103 years) were Covid-19-positive.They were significantly younger, and had higher rates of ADHD (adjOR 1.58 (95% CI 1.27–1.96, p < .001) than Covid-19-negative subjects. The risk for Covid-19-Positive was higher in untreated-ADHD subjects compared to non-ADHD subjects [crudeOR 1.61 (95% CI 1.36–1.89, p < .001)], while no higher risk was detected in treated ones [crudeOR 1.07 (95% CI 0.78–1.48, p = .65)]. Conclusion: Untreated ADHD seems to constitute a risk factor for Covid-19 infection while drug-treatment ameliorates this effect.